Math and Arithmetic
Algebra
Calculus

What does 12x squared plus 18 divided by 3x squared plus six equal?

123

Wiki User

(12x2 + 18) / (3x2 + 6)

= (4x2 + 6) / (x2 + 2)

๐
0
๐คจ
0
๐ฎ
0
๐
0

Related Questions

4x2+12x = 4x(x+3) when factored

If this is algebra then; 3x plus 12x = 15x

12x and then the squared. (the little two)

9x2...I guess that means 9x squared ? The problem: 9x(squared)+12x+4 Here's the answer: (3x+2)(3x+2) or even more simplified: (3x+2) squared

I assume you mean (x+10)(x+2) This would equal x^2+12x+20 x^2 means x squared

x2+12x+11=0 (x+11)(x+1)=0 x=-11 or x=-1

12x-4y+9z+2y =12x-2y+9z

Factor. X^2 + 12X X(X + 12) = 0 X = 0 ------------- X + 12 = 0 X = - 12 --------------

The factors of 5 are 1 and 5. 12 = 2 x 5 + 2 x 1, therefore: 4x2 +12x +5 = (2x + 1)(2x + 5)

x2 + 12x + 36 = 0(x + 6) (x + 6) = 0x+ 6=0 ;x + 6 = 0x = -6 ; x = -6

it depends on what 4x-12x is equal to

9726x ^ 8 = 1679616x12x ^ 3 = 1728x1679616 / 1728x = 972

It can't be factored because its discriminant is less than zero

That doesn't factor neatly. Applying the quadratic equation, we find two real solutions: (-2 plus or minus the square root of 5) divided by 3x = 0.07868932583326327x = -1.4120226591665965

The constant (no x) part must be equal to the square of half the linear part, that is, (12/2)2.

3x multiplied by (12x plus 9) is:3x(12x + 9)= (3x * 12x) + (3x * 9)= 36x2 + 27x

If you mean y = -12x+3 then it is a straight line equation whereas -12 is the slope and 3 is the y intercept

Math and ArithmeticAlgebra

Copyright ยฉ 2020 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.